Fisiologi Pemberian Larutan Oral Karbohidrat pada Pasien yang akan Menjalani Operasi Elektif - Sar, Djayanti; Kurniawati, Juni; Sunantara, I Gusti Ngurah Putu Mandela Agatha (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
Surgery is a combination of anesthesia, drugs, trauma, blood loss. Apart from that, patient preparation before surgery which is routinely carried out such as fasting for 6- 8 hours is also part of the operation. This condition can disturb the balance in the body. The metabolic state of the preoperative patient must be optimized in preparation for surgery. The patient should be in a sufficiently anabolic rather than starved and catabolic state. The typical fasting period of 8 hours before surgery forces the metabolism into a catabolic state. Administration of an oral carbohydrate solution before surgery helps to keep the body in the desired anabolic state. The usual administration is 2-3 hours before the operation, the patient will be given an oral carbohydrate solution. Therefore, this paper is made to determine the physiology of giving oral carbohydrate solution as a preoperative management for patients who will undergo surgery